The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1038/srep37859
|View full text |Cite
|
Sign up to set email alerts
|

Profilometry of thin films on rough substrates by Raman spectroscopy

Abstract: Thin, light-absorbing films attenuate the Raman signal of underlying substrates. In this article, we exploit this phenomenon to develop a contactless thickness profiling method for thin films deposited on rough substrates. We demonstrate this technique by probing profiles of thin amorphous silicon stripes deposited on rough crystalline silicon surfaces, which is a structure exploited in high-efficiency silicon heterojunction solar cells. Our spatially-resolved Raman measurements enable the thickness mapping of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…When analyzing thin films, this remaining signal from the substrate is a distraction at best and the source of significant error at worst (e.g., if the thin film is μc‐Si:H), and thus RCD is not helpful in determining the minimum tolerable film thickness for Raman analysis. (Note that Ledinský et al recently demonstrated a particular case in which signal from the substrate can be advantageous: They calculated the thickness of a‐Si:H films from the remaining Raman signal from the substrate ).…”
Section: Resultsmentioning
confidence: 99%
“…When analyzing thin films, this remaining signal from the substrate is a distraction at best and the source of significant error at worst (e.g., if the thin film is μc‐Si:H), and thus RCD is not helpful in determining the minimum tolerable film thickness for Raman analysis. (Note that Ledinský et al recently demonstrated a particular case in which signal from the substrate can be advantageous: They calculated the thickness of a‐Si:H films from the remaining Raman signal from the substrate ).…”
Section: Resultsmentioning
confidence: 99%
“…Second, in the tunnel-IBC design the deposited Si:H(p) layer has a uniform thickness. This eliminates the problem of insufficient charge-collecting film thickness along the perimeter of the contacts 43,44 that is associated with the tapered doped layer profiles produced by in situ shadowmask patterning 45,46 .…”
mentioning
confidence: 98%
“…While this is very advantageous, the industrial compatibility of using reusable shadow masks is debatable. Moreover, depositions through masks lead to tapered profiles of deposited films and require proximal contact of wafers with the masks …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, depositions through masks lead to tapered profiles of deposited films and require proximal contact of wafers with the masks. 14 Another popular "litho-free" alternative to patterning, which is contact-less and also drastically reduces the number wet chemical steps, is laser ablation-assisted patterning. [15][16][17][18][19][20] In this approach, the pattern is often directly structured onto a sacrificial mask layer on top of the a-Si:H stack to be patterned.…”
Section: Introductionmentioning
confidence: 99%